Essays on disability and wellbeing in Uganda - Abubakar, Aisha Mohammed (2022)
The thesis introduces three independent but related empirical studies on disability and wellbeing in Uganda. The first essay evaluates the short-term health and economic impacts of providing orthotic equipment to adults with lower limb disability using unique data collected during an orthotic equipment intervention between 2012 and 2013. The study adopts a before-after estimation strategy to examine changes to: (i) functional mobility and (ii) labour market outcomes, including the type of employment and monthly earnings. One year after the intervention, the effects are noticeably gendered; men exhibit an improvement in their level of functional mobility, while women face little change or a reduction in their mobility levels. In terms of labour market outcomes, for men, the intervention leads to an increase in monthly earnings, which is partly due to a switch from self- to wage employment. Earnings increase for women, although the overall effect is much smaller. Taking into account the intensity of equipment use, the Wald estimates reveal larger marginal effects on both mobility and earnings.